Effects of Hydroxyl Group on the Interaction of Carboxylated Flavonoid Derivatives with S. Cerevisiae α-Glucosidase - Lu, Huining; Qi, Yanjiao; Zhao, Yaming; Jin, Nengzhi (Current Computer - Aided Drug Design, 2020)
Introduction: Carboxyalkyl flavonoids derivatives are considered as effective inhibitors in reducing post-prandial hyperglycaemia. Methods: Combined with Density Functional Theory (DFT) and the theory of Atoms in Molecules (AIM), molecular docking and charge density analysis are carried out to understand the molecular flexibility, charge density distribution and the electrostatic properties of these carboxyalkyl derivatives. Results: Results show that the electron density of the chemical bond C14-O17 on B ring of molecule II increases while O17-H18 decreases at the active site, suggesting the existence of weak noncovalent interactions, most prominent of which are H-bonding and electrostatic interaction. When hydroxyl groups are introduced, the highest positive electrostatic potentials are distributed near the B ring hydroxyl hydrogen atom and the carboxyl hydrogen atom on the A ring. It was reported that quercetin has a considerably inhibitory activity to S. cerevisiae α-glucosidase, from the binding affinities, it is suggested that the position and number of hydroxyl groups on the B and C rings are also pivotal to the hypoglycemic activity when the long carboxyalkyl group is introduced into the A ring. Conclusion: It is concluded that the presence of three well-defined zones in the structure, both hydrophobicity alkyl, hydrophilicity carboxyl and hydroxyl groups are necessary.
Keywords: carboxyalkyl flavonoids